Does national service increase civilian wages? - Goh, Gabriel Jian Nan (2015)
All males in Singapore must undergo two years of mandatory conscription known as National Service. We examined the returns to National Service across two different conscription schemes in Singapore, each with varying service durations. Using Two-Stage Least Square to treat for endogeneity, we found the returns to National Service to be positive across both conscription schemes. This suggests that National Service provides men with general training that is transferable to the civilian labor market.